Hubungan Beban Kerja Dengan Status Kesehatan Fisik Mitra Pengemudi Gojek di Kota Medan Tahun 2025: Studi Cross-Sectional - Hudeni Rizki; Dealita Khairani Daulay; Evlindari Sentani Daulay; Yanty Gurning (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The rapid expansion of application-based transportation has pushed online motorcycle-taxi driver-partners, including two-wheeled Gojek drivers, to work long hours in pursuit of order targets and bonuses, creating a risk of excessive workload that may reduce physical health status; quantitative evidence using a composite health measure among Gojek partners in Medan remains scarce. This study analyzed the association between workload level and physical health status among Gojek driver-partners in Medan City in 2025. An analytical cross-sectional study was conducted on 60 active two-wheeled Gojek driver-partners selected through accidental sampling; sample size was calculated using the Slovin formula. Workload was measured with the NASA-Task Load Index, and physical health status as a composite of work fatigue (IFRC) and musculoskeletal complaints (Nordic Body Map). Data were analyzed using a Cochran-Armitage trend test, Fisher's exact test, and Spearman's rank correlation. Most respondents (58.3%) experienced high workload and 45.0% had poor physical health status. Higher workload was significantly associated with poorer physical health status (trend test p=0.028; Spearman rho=0.39, 95% CI 0.15-0.59, p=0.002). Regulating working hours, scheduled rest breaks, and ergonomic education should be prioritized as preventive measures.